Police Impersonation: Pretenses and Predators - Rennison, Callie Marie (American journal of criminal justice, 2012)
Empirical research on police impersonation is rare. This research employs quantitative and qualitative methodologies on 2002–2010 police case files describing impersonation incidents from three police agencies to provide an understanding of the individual and situational constructs associated with police impersonation. Research objectives included: exploring incident characteristics, comparing incidents to national violent crime statistics; and identifying common themes. Results show that police impersonation incidents, offenders, and victims are unique, particularly when compared to national data. Qualitative analysis identified three major themes related to tactics, motivations, and typology. The research offers a framework for establishing policy recommendations.